The Effects of Child Grooming in Priscilla (2023): Psychological Approach - Jacinta Maharani Mulawarman; Jonathan Irene Sartika Dewi Max (Fakultas Ilmu Budaya Universitas Mulawarman, 2026)
This research analyzes the stages and psychological effects of child grooming in Priscilla (2023), which portrays an unequal relationship between a minor and an adult public figure. The film depicts grooming through emotional manipulation rather than explicit abuse. As an autobiographical adaptation of Priscilla Presley’s life, it centers the victim rather than the perpetrator. The study employs McAlinden’s theory of child grooming, the grooming stages model by Winters, Jeglic, and Kaylor, and Elliot and Briere’s indicators of psychological effects. Using a qualitative method and Wellek and Warren’s psychological approach to literature, the analysis applies Petrie and Boggs’ framework of conflict and characterization in film. The findings identify five manipulation stages, which are victim selection, gaining access and isolating a child, trust development, desensitization to sexual content and physical contact, and maintenance following the abuse, and six psychological effects, which are anxiety, depression, dissociation, sexual problems, sleep disturbance, and post-traumatic symptoms. These findings appear through both internal and external conflicts, with internal conflict being the most dominant. Characterization reveals Priscilla’s passivity, emotional fragility, and dependency on Elvis. This study demonstrates that film, as a form of literary work, can represent the emotional, behavioral, and cognitive consequences of child grooming through its intrinsic elements of conflict and characterization.